Partial replacement of an artificial nectar diet with native browse for feather‐tail gliders (Acrobates pygmaeus) in captivity. Issue 4 (27th February 2013) - Herrmann, Ella A.; Herrin, Kimberly Vinette; Gleen, Wendy; Davies, Paul; Stapley, Rodd; Stebbings, Vanessa; Wiszniewski, Joanna; Spindler, Rebecca; Faichney, Graham J.; Chaves, Alexandre V.
Abstract Captive‐bred feather‐tail gliders (Acrobates pygmaeus) housed at Taronga Zoo have had a long history of eye cholesterol plaques that may be associated with a largely sugar‐based diet such as artificial nectar. The gliders also have prolonged periods of reduced activity when they are not visible in exhibits. This may be due to the ad libitum supply of an energy rich feed and reduced need to forage. This study examined behavioral and physiological changes associated with supplementing the high sugar‐based diet with two species of native browse. The experiment was conducted over two consecutive periods of 3 weeks and consisted of two treatment groups: one group was offered the artificial nectar only, while the other group was offered the artificial nectar supplemented with a variety of native flowers. Live weight was recorded weekly. There was no change (P > 0.10) in artificial nectar intake with the supplementation of native browse in the diet. Blood metabolites (cholesterol, triglycerides, glucose) tested for the two groups had no differences (P > 0.10) between treatments. Upon examination, there were no signs of tooth decay or cholesterol plaques in all animals throughout the experiment. Feed intake and behavior were recorded via sensor cameras. There was an increase (P < 0.05) in the daily foraging activity of gliders supplemented with native flowers compared to gliders fed the artificial nectar alone. In conclusion, supplementing to provide a more native diet to A. pygmaeus enhanced their natural foraging behavior, suggesting that it may result in long‐term improvements in their health. Zoo Biol. 32:394–399, 2013. © 2013 Wiley Periodicals Inc.